Feature extraction and image processing - Nixon, Mark S. (Newnes, 2002)
Focusing on feature extraction while also covering issues and techniques such as image acquisition, sampling theory, point operations and low-level feature extraction, the authors have a clear and coherent approach that will appeal to a wide range of students and professionals. This is an ideal module text for courses in artificial intelligence, image processing and computer vision. It is an essential reading for engineers and academics working in this cutting-edge field. It is supported by free software on a companion website.